Expression of TGF-β Signaling Regulator RBPMS (RNA-Binding Protein With Multiple Splicing) Is Regulated by IL-1β and TGF-β Superfamily Members, and Decreased in Aged and Osteoarthritic Cartilage. (October 2016) - Shanmugaapriya, S.; van Caam, A.; de Kroon, L.; Vitters, Elly L.; Walgreen, B; van Beuningen, H.; Davidson, E. Blaney; van der Kraan, Peter M.
Objective: RNA-binding protein with multiple splicing (RBPMS) has been shown to physically interact with Smads and enhance transforming growth factor-β (TGF-β)–mediated Smad2/3 transcriptional activity in mammalian cells. Objective of this study was to examine whether expression of RBPMS is regulated by interleukin-1β (IL)-1β and TGF-β superfamily growth factors and whether expression of RBPMS is altered during aging and experimental osteoarthritis. Methods: Expression of RBPMS protein was investigated in chondrocyte cell lines of murine (H4) and human (G6) origin using Western blot analysis. Regulation of RBPMS expression in H4 chondrocytes at mRNA level was done by reverse transcriptase–quantitative polymerase chain reaction. Furthermore, characterization of Smad signaling pathways regulating RBPMS expression was performed by blocking studies using small molecule inhibitors or by transfection studies with adenoviral vector constructs (constitutive-active ALK1 and constitutive-active ALK5). Expression of RBPMS in cartilage of different age groups of C57BL/6N mice (6 months and 20 months) and in a surgically induced osteoarthritis (OA) mouse model was analyzed using immunohistochemistry. Results: RBPMS was shown to be expressed in chondrocytes and cartilage of murine, human, and bovine origin. TGF-β inhibited RBPMS expression while BMP2 and IL-1β increased its expression. TGF-β-induced inhibition was blocked by ALK5 inhibitor. Overexpression of ca-ALK1 stimulated RBPMS expression. Moreover, RBPMS expression was found to be reduced with ageing and in OA pathogenesis. Conclusions: Expression of RBPMS in chondrocytes is regulated by TGF-β superfamily members and IL-1β, indicating a counter-regulatory mechanism. Expression of RBPMS, in cartilage and its reduction during ageing and OA might suggest its potential role in the maintenance of normal articular cartilage.